2010
DOI: 10.1086/656218
|View full text |Cite
|
Sign up to set email alerts
|

The Cocoon of the Fossorial FrogCyclorana australisFunctions Primarily as a Barrier to Water Exchange with the Substrate

Abstract: Studies of evaporative water loss using streams of dry air in the laboratory have demonstrated reduced rates in various taxa of cocooned frogs. However, because the cocoon is formed in subterranean burrows with humid microclimates and no air flow, loss of water by evaporation is likely to be negligible. In contrast, although potentially important, the influence of the cocoon on water exchange with the soil surface has not been characterized. In dry soils, there is a sizable water potential gradient between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The accumulation of the layers is accompanied by a rapid decrease in evaporative water loss in laboratory conditions, reaching a minimum after about a month (McClanahan et al, 1983). In natural conditions it has been believed that the cocoon functions by preventing water loss to the dry soil (Shoemaker et al, 1992), as recently demonstrated for Litoria australis (Reynolds et al, 2010).…”
Section: Dry Habits Die Hard: Diversification In Semiarid Environmentsmentioning
confidence: 91%
“…The accumulation of the layers is accompanied by a rapid decrease in evaporative water loss in laboratory conditions, reaching a minimum after about a month (McClanahan et al, 1983). In natural conditions it has been believed that the cocoon functions by preventing water loss to the dry soil (Shoemaker et al, 1992), as recently demonstrated for Litoria australis (Reynolds et al, 2010).…”
Section: Dry Habits Die Hard: Diversification In Semiarid Environmentsmentioning
confidence: 91%
“…Naked mole-rats ( Heterocephalus glaber ) have the ability defined at point 2, changing metabolism to survive underground in low-oxygen environments [ 14 ]. Australian frogs ( Cyclorana australis ) belong to point 3, creating a new environment rich of mucus to prevent skin from drying out in the hot climate [ 15 ]. Other species, such as penguins in Antarctica, carry out the amazing collective adaptation of point 4, crowding together to share their warmth and survive glaciation.…”
Section: About Species and Intelligence: A Necessary Premisementioning
confidence: 99%
“…The cocooned Leptodactyolus fuscus was discovered during the dry season when there had been successive days without rain. This cocoon seems to act as physical barrier preventing water loss (Reynolds et al 2010 (Cartledge et al 2006, Tracy et al 2007, and South America [ceratophryids Lepidobatrachus llanensis Reig andCei, 1963 andCeratophrys ornata (Bell, 1843)] (McClanahan et al 1976(McClanahan et al , 1983. Given the distant relationships of these lineages, it seems likely that ability to form such cocoon evolved independently in the various groups and may be more widespread among aestivating anurans than currently thought Hillman 1981, Faivovich et al 2014).…”
mentioning
confidence: 98%
“…It follows that most anurans occurring in the seemingly unfavorable conditions of the Caatinga have mechanisms to protect themselves from desiccation in the surface soil (Prado 2003, Navas et al 2004. Anurans employ three main strategies to avoid drying effects of the surface soil; they can burrow deep in the soil, accumulate urea in body fluids, and form cocoons (Shoemaker et al 1969, Shoemaker 1988, Cartledge et al 2006, Reynolds et al 2010. Typically, most Caatinga anurans also have additional adaptations.…”
mentioning
confidence: 99%